The House Types of Settlements in The RiverBank Wetland; The Factual Conditions and The Recommendations - Maya Fitri Oktarini (Tesa Arsitektur, 2018)
A riverbank wetland has an important ecosystem service, so that should be a city conservation area. The settlements on wetland riverbanks would decrease the ecosystem services. But for some cities, it is difficult to avoid. To reduce the damage to the ecosystem services, it is necessary to identify the ideal development according to the ecosystem approach. This study identifies the gap between the factual house type and the ideal type according to the ecosystem approach. The factual home types were identified through field observations, whereas the types of recommendations were identified based on an assessment of the experts. The results indicated that there was a gap of the house types between the factual and the recommendations. Therefore, the planning should adjust the house types between the factual and the recommendation of the ecosystem approach. The settlement planning that equilibrates the community needs and the sustainability of ecosystem services.